The Internationalization of SMEs in Central Europe and Its Impact on Their Methods of Risk Management - Zuzana Virglerova; Muhammad Asif Khan; Raimonda Martinkute-Kauliene; Sandor Kovács (Amfiteatru Economic)
The international business environment is very competitive, and enterprises should be aware of how to manage business risks, which methods to choose, and what impact these risks have on the sustainability of these methods and on the whole system. The aim of this article is to analyse the impact of the internationalization of SMEs on risk management and define the differences in perceptions of the importance of sustainability regarding this system. Data from an extensive research study in V4 countries (Czech Republic, Hungary Slovakia, Poland) were analysed. Data were collected through on-line questionnaire in 2018, and a total of 1781 valid responses by SMEs were included in this research. To fulfil the research aim, three hypotheses were established. The odds ratio was calculated for the effect of company type (international x domestic) on the different individuals responsible for risk management. The Tarantula similarity measure was calculated to measure the strength and pairwise relationships between risk reducing strategies and risk management techniques. The Chi-Square test was applied to assess differences between variables. The results show that a specialized risk manager is authorized to deal with risk management in international companies more often than in domestic companies. There are also differences in the relationship between risk managing techniques and risk reducing strategies, depending on the presence of the business on international market. Companies in the international market are more focused on methods of risk management which support sustainability and their system of risk management has a more stable future.